Pengaruh Model Project Based Learning Terhadap Hasil Belajar Materi Ekosistem Pada Peserta Didik Kelas V di SDN Ganrang Jawa 1 Kecamatan Pattalassang Kabupaten Gowa - Nur Fadliah; Ma’ruf Ma’ruf; Hilmi Hambali (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
This study aims to determine the effect of the Project Based Learning Model on the learning outcomes of eco-system material in fifth grade students at SDN Ganrang Jawa 1, Pattalassang District, Gowa Regency. The method used in this study is quasi-experimental (Quasi Experiment). This study used two sample groups, namely the experimental group of 25 students and the control group of 24 students. The instruments used in this study were multiple choice tests and observation sheets which were then tested in a class with a non-equivalent control group design. This is shown by the results of the t test, namely at the significance level α = 0.05, the average of the experimental group was 83.52 and the control group was 82.33. Based on the hypothesis test based on the df value which is 96 with a level value of 0.05 showing the result is 91,004. because t count = 24,266 > t table = 91,004, until H0 is rejected while H1 is accepted. Thus it can be concluded that the use of the project based learning model has an effect on student learning outcomes in ecosystem material at SDN Ganrang Jawa 1, Pattalassang District, Gowa Regency.